The Influence Of Attitude, Behavior And Organizational Culture On Employee Performance At Bpjs Ketenagakerjaan Muaraenim Branch - Sari, Nyimas Nurmelita; Widiyanti, Marlina; Yusuf, Muhammad; Adam, Mohamad (UNIVERSITAS PAKUAN, 2019)
This research was conducted aiming to determine the effect of attitudes, behavior and organizational culture on employee performance at the Muaraenim branch of Employment BPJS. The population in this study were all 157 employees of the Muarenim branch of the Employment BPJS. The results of multiple linear analysis show that attitudes, behavior and organizational culture have a positive and significant effect on employee performance at the Muaraenim branch of the Employment BPJS. Attitude, it is necessary to evaluate the facilities needed by employees, such as adding or upgrading computers/laptops as well as facilities and infrastructure that are tailored to the needs of employees. Behavior, there are several relationships between fellow employees and employees with superiors that are not well established. Organizational culture, with frequent changes in leadership, requires employees to get used to the established work rhythm.